Oona and the shark - DiPucchio, Kelly (Katherine Tegen Books, an imprint of HarperCollins Publishers, 2022)
Oona the mermaid is friends with everyone, but when her attempts to befriend a shark with sensory issues fail miserably she realizes what may be fun for her may be overwhelming for him.